2001
DOI: 10.1029/2001jd900169
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol optical depths over peninsular India and adjoining oceans during the INDOEX campaigns: Spatial, temporal, and spectral characteristics

Abstract: which is attributed to air trajectory effects. AngstrOm parameters, deduced from optical depth spectra, reveal a high value of o• (-0.9) for north of the ITCZ, while for the south oc is negative, indicating a change in the aerosol size distribution. Accumulation aerosols dominate in the north, while concentration of coarse aerosols remain nearly about the same, except very close to the coast. A north-south gradient in aerosol optical depth, with scaling distance of -1000 to 2000 km at shorter wavelengths and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
73
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 24 publications
(10 reference statements)
7
73
1
Order By: Relevance
“…Lower values of α indicate larger abundance of super micron aerosols (Satheesh and Moorthy, 1997). As the smaller particles over continental locations are primarily produced by anthropogenic activities, the value of α can be considered as a measure of anthropogenic influence (Moorthy et al, 1999(Moorthy et al, , 2001Moorthy and Satheesh, 2000). Our observations have shown that α normally decreases drastically from ∼1.0 during April 2001 to ∼0.15 during June 2001.…”
Section: Size Characteristicsmentioning
confidence: 57%
See 1 more Smart Citation
“…Lower values of α indicate larger abundance of super micron aerosols (Satheesh and Moorthy, 1997). As the smaller particles over continental locations are primarily produced by anthropogenic activities, the value of α can be considered as a measure of anthropogenic influence (Moorthy et al, 1999(Moorthy et al, , 2001Moorthy and Satheesh, 2000). Our observations have shown that α normally decreases drastically from ∼1.0 during April 2001 to ∼0.15 during June 2001.…”
Section: Size Characteristicsmentioning
confidence: 57%
“…Since the sources of anthropogenic aerosols are located primarily over land, the radiative forcing of aerosols is larger over land (Charlson et al, 1991(Charlson et al, , 1992Kaufman et al, 1998;Subbaraya et al, 2000;Moorthy et al, 2001;Babu et al, 2002). Moreover, land responds more quickly than ocean to any change in radiation flux due to its low heat capacity compared to the ocean (Heintzenberg et al, 1997;Satheesh, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…1 indicates significantly high values in aerosol spectral optical depths during 1997 and 1999. Moorthy et al (2001), based on the NCEP wind data, as well as meteorological reanalysis, have shown that the when the spectral optical depths were close to the mean values, as in 1998, the Inter-tropical convergence zone (ITCZ), in general, has been far more south than in 1997 and 1999. In 1999, the ITCZ was situated just south of the equator.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that in spite of a very small contribution to the mass of the atmosphere, it is found that aerosols significantly influence the Earth's radiation budget and climate Crutzen and Andrae, 1990;Charlson et al, 1992;Andreae, 1995;Subbaraya et al, 2000;Moorthy et al, 2001;Devara et al, 2005). Aerosols produce direct radiative effects in the atmosphere by increasing backscattered solar radiation and by absorbing solar and long wave radiation (Satheesh and Ramnathan, 2000;Houghton et al, 2001).…”
Section: Introductionmentioning
confidence: 99%